Follow effect of low cost glass fibre reinforced polymer (GFRP) on the performance of concentrically loaded concrete column - Pannirselvam N,; Sudarsan J S,; Nithiyanantham S, (Vietnam Journal of Science and Technology, 2023)
(FRP) plays a major role in the strengthening of existing structures due to the age of the structure or natural calamities like earthquakes, floods, cyclones, etc. For reducing the size of structural members, the FRP wrapping assists to achieve the performance of the structure.  Concrete is widely used due to its advantages and FRP is added to improve its quality in terms of strength. A study has been conducted on 21 cylinders based on their slenderness ratio. The slenderness ratios in the columns were 8, 16, and 24. At thicknesses of 5 mm and 7 mm, two types of wrap materials (UDCGFRP) and (WRGFRP)] were employed. Up to the point of failure, the columns were subjected to monotonic axial compressive force. The column’s yield loads, and ultimate load, were deduced from the load-deflection curves. The overall, uni-directional cloth provided the most effective confinement and led to a highly desirable failure mechanism, which was a gradual process.